Sleep parameters in children who stutter: A comparison with children who do not stutter using actigraphy - Couto, Maria Clara Helena [UNESP]; Canhetti de Oliveira, Cristiane Moço [UNESP]; Meneses da Silva, Isabella [UNESP]; de Souza, Ana Luiza Decanini Miranda [UNESP]; Proença, Mahara [UNESP]; Barreira, Tiago V.; Pinato, Luciana [UNESP] (Elsevier, 2025)
Purpose: This study aimed to compare objective sleep parameters in children who stutter (CWS) with those in children who do not stutter (CWNS) using actigraphy. Previous research, mainly relying on subjective methods such as questionnaires and sleep diaries, has highlighted the high prevalence of sleep disorders in individuals who stutter. Methods: Sleep parameters, including sleep onset latency, sleep efficiency, sleep duration, and total sleep time, were objectively measured using actigraphy over 14 consecutive days. The study included 30 CWS (aged 4–12 years) and 21 CWNS (also aged 4–12 years). Data were analyzed with SPSS Statistics 28.0 software, expressed as medians with interquartile ranges (25–75 %). Group comparisons were conducted using the Mann-Whitney test. The significance level for all statistical tests was set at p < 0.05. Results: CWS exhibited significantly longer sleep onset latency (p < 0.001) and lower sleep efficiency (p = 0.01) compared to CWNS. No significant differences were observed in total sleep time or sleep duration between the groups. Discussion: This study provides objective evidence that CWS experience specific alterations in sleep parameters, particularly in sleep onset latency and sleep efficiency. This suggests a higher prevalence of sleep disturbances within this population. These findings highlight the importance of integrating sleep assessments into the clinical management of stuttering to improve therapeutic outcomes.
Keywords: Actigraphy; Evaluation Study; Sleep; Sleep Disorders; Stuttering